PEMBELAJARAN MATEMATIKA MENGGUNAKAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBENTUK KOMIK - Suhartati Suhartati; Yulis Jamiah; Silvia Sayu (Jurnal AlphaEuclidEdu, 2021)
This research aims to know the effectiveness of LKPD from comic in mathematics teaching a algebra’s subject for students of SMA Negeri 3 Pontianak. This research is classified as a pre-experimental in form of one shot case study design. The population of this research were students of eleven grade science program, and the samples is 1 class of students in eleven grade science program. The sample were selected by conducting purposive sampling. The revenue of  data analysis point out that the learning activity was very active with the average student learning activities obtained by 89.35%, the study result was reached. Student gave a great feedback, the implementation of learning management by teachers in learning mathematics was classified as ‘very good’. Based on the research findings that four cathegories of effectiveness was reached, therefore the application of  LKPD from comic was effective in mathematic teaching a algebra materials to the students grade XI science 2 of SMA Negeri 3 Pontianak.Keywords: Effectiveness, LKPD, Comic